Skill Artificial Intelligent Supported Duolingo: Enhancing Students’ Speaking Skills and Reducing Speaking Anxiety in Vocational Education - Luky Arika Pusparini; Lusia Maryani Silitonga; Senowarsito (Universitas Muhammadiyah Surakarta, 2025)
The integration of artificial intelligence (AI) into language education has introduced adaptive, interactive learning experiences that enhance student engagement, particularly in English language instruction. For vocational students, strong communication skills are essential alongside technical competencies. However, challenges such as limited speaking exposure, low self-confidence, and high anxiety persist, often intensified by traditional grammar-focused teaching methods. This study investigates the effectiveness of AI-supported Duolingo in enhancing speaking skills and reducing speaking anxiety among 64 students at SMKN 1 Kunduran, a vocational high school in Indonesia. Utilizing a mixed-methods approach, quantitative data were analyzed using ANOVA and ANCOVA, while qualitative insights were gathered through student interviews and analyzed via MAXQDA. Results show that Duolingo significantly improved students’ speaking skills such as their vocabulary, pronunciation, and fluency, with the experimental group consistently outperforming the control group. The platform’s AI-driven speech recognition and instant feedback mechanisms fostered a low-anxiety environment, increasing learners’ speaking confidence. Student perceptions further highlighted Duolingo’s ease of use, engaging gamification, and collaborative learning benefits. Nevertheless, the study reinforces the importance of real-life speaking interactions to achieve comprehensive fluency.